Judicial Control of Special Investigative Measures of Security Services in the Republic of Serbia - Mirković, Vladan M (NBP. Nauka, bezbednosti, policija, 2017)
The rule of law, as an ideal form of government, represents the rule of the people through a democratically established legal order and the order of legal norms in order to achieve all social values. Security is one of the basic assumptions of the rule of law, since the system of legal norms can be applied only in regular situations or in situations where all social values ​​are protected to the extent necessary. It can be concluded that security is the value by itself, and it has an instrumental character since it creates the basis for the realization of all others values. Sometimes different situations can interfere with the normal functioning of socio-political processes, which can undermine the basic assumptions of the rule of law. The activities of organized criminal groups or terrorist organizations lead to disruptions of political, economic and social processes, since these activities cause the regular and anticipated ways of solving issues (public and private) to be deformed. Corruption, insecurity, uncertainty and ultimately, fear, appear as everyday characteristics of social relationships. A society weakened in such way constitutes an ideal framework for those whose destructive activities create situations in which the existence of society and the state is directly threatened by the combined action of external and internal carriers of threat. This primarily refers to the operation of foreign intelligence services that will easily find domestic citizens in these socio-political circumstances through which they will achieve subversive or intelligence goals. In order to prevent these, but also other threatening phenomena, security services, as specialized state authorities, undertake a series of measures. One of the most effective methods of security services is the application of special investigative measures. Such measures deviate from the guaranteed human rights to a certain extent, but on the other hand the national security interests justify the application of measures for preventive purposes, but only in exceptional situations and under the stipulated conditions. There are three security services in the Republic of Serbia, and all of them apply such measures in their work, but the application of these measures is under different legal regimes. The measures taken by the BIA are fully subject to judicial approval, which greatly contributes to the protection of human rights, since the court decides on the measures that deviate from human rights as an independent and autonomous state body. The measures taken by the two military services (VBA and VOA) are only partially subject to judicial approval, which can be justified by the theoretical division into measures that deviate less and measures that deviate more from human rights. However, the role of the court should not be reduced to the mere approval of the measure. Active role of the court during the entire process of application of the measure (only those which are subjected to judicial approval) should become a standard in our country. The Court, as an independent and autonomous state body, through decision-making and supervision of the implementation of the measures should ensure the legality and, therefore that the goal of the measure is achieved. In this way, the court is the guarantor that the measures will be used to remove the circumstances that have called into question the normal functioning of the state, and that they will not become a means of dictatorship and the elimination of political opponents.